Cooperativity in Adhesion Cluster Formation during Initial Cell Adhesion - Selhuber-Unkel, Christine (The Biophysical Society, 2008)
We have studied the initial phase of cell adhesion as a function of the lateral organization of individual integrin molecules with single-cell force microscopy. Nanostructures, consisting of hexagonally ordered gold dots, were prepared with diblock-copolymer micelle lithography and functionalized with arginine- glycine-aspartate peptides, thus defining integrin position with nanometer resolution. Adhesion strength was characterized with an atomic force microscope and both cell detachment forces and work of detachment showed a reinforcement of adhesion if the distance between integrin molecules was <70 nm. This reinforcement had already occurred at cell-substrate contact times <5 min. We believe our results show quantitatively the relevance of the distance between adjacent integrin binding sites rather than their density. Furthermore, we propose a model describing the cooperative stabilization of early integrin clusters as a function of receptor patterning at the nanoscale.